Knowledge, attitude and practice towards self-medication among pharmacy students in tertiary care hospital - Selvam, Sindhu; Srinivasan, Shakthi Priyan; Krishnamoorthy, Deena; Baskar, Sowmiya; Mohudeen, Saddick; Panneer, Abinaya Jayakrishnan (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Self-medication, which is when the public treats health problems on their own without consulting a doctor, is very common. The objective of this study is to analyze pharmacy students' self-medication practices, attitudes, and knowledge in a tertiary care hospital. Methods: Data will be collected from the B. Pharmacy, M. Pharmacy and Pharm. D with their consent by request to them to complete the questionnaire (self-administrated). Results: A total of 339 responses from participants were prospectively collected and documented. The participant characteristics such as demographic information (age, gender, and education) was collected. Conclusions: Insufficient understanding regarding appropriate self-medication exists, yet changes can be made in this situation with the existing positive attitude of the respondents. Seminars and workshops can be utilised to effectively distribute knowledge to students, while implementing robust policies to curb the increasing trend.